Antibody Response of Broiler Chickens against Eight Commercial Infectious Bursal Disease Live Vaccines tested by ELISA - I.M. D. AL-Mayah; A. A. S. AL- Mayah (Mirror of Research in Veterinary Sciences and Animals, 2013)
This study was designed to investigate the antibody response of broiler chickens against eight commercial IBD live vaccines. A total of 460 one- day Ross broiler chicks were divided to 9 groups, eight groups were vaccinated with IBD live vaccines and the last one was served as control. Four groups were vaccinated with intermediated vaccines, whereas the other fourth were given intermediated plus vaccines. All vaccinated groups were administrated at 14th day of age via drinking water route. Maternal derived antibody (MDA) and post- vaccination antibody response were tested by ELISA. Blood samples were collected at one-day old and at 21st, 28th and 35th day of age post- vaccination. Indirect ELISA test revealed that the mean of maternal derived antibody was 4852±745. Significant differences (P<0.05) among means of antibody titers of all vaccinated groups were found at 21st ,28th and 35th day of age compared with that of control group. The results also showed that groups which were vaccinated with intermediated plus vaccines (E and H vaccines) exhibited high level of antibody especially groups 5 and 8 than those which vaccinated with intermediate vaccines. In conclusion, Intermediate plus vaccines induced higher antibody titers than other vaccines, although some intermediate vaccines induced similar titers of antibody E and H vaccines which were administered to groups 5 and 8 respectively induced better antibody titers.